Emotional Distress in the Relationship of Caregivers and Institutionalized Babies - Nascimento, Rosemeire Aparecida do; Furutani de Oliveira, Mirian Akiko; Benute, Gláucia Rosana Guerra; Landmann, Andrea Nogueira; Galo, Fernanda; Borges, Thames Waléria (Frontiers in Psychiatry, 2020)
Institutionalization is an exceptional and temporary measure that occurs when there is a violation of rights; lasting until the family reintegration or, in this impossibility, the placement in substitute family through adoption. Among the main reasons for institutionalization in Brazil are: financial difficulties, abandonment, domestic violence, drug addiction, homelessness of the responsible for the child, sexual abuse and loss of parents by death or imprisonment. Although children and adolescents have their rights assured when they are institutionalized, the care provided in these spaces does not include all their needs and demands, which may damage their affective-relational development. Maternal deprivation in first years of life can be detrimental to children's development, if not provided by adequate substitute care. Therefore, to understand which place the institutionalized baby occupies in the imaginary of social caregivers and, from this, how is established the relationship regarding the care, is fundamental to assess and address the risk factors in child development at this stage of life and in situation of institutionalization. This is an exploratory and descriptive study, developed in childcare institution, located in São Paulo - Brazil - capable of accommodating up to 20 babies between 0 and 2 years old. Data collection was performed with nine employees, eight social caregivers and one general service assistant who work directly in the care of the these babies. Drawing-Story with Theme Procedure were used. Qualitative analysis was based on Interpretive Phenomenological Analysis. The appreciation of the 9 applied Drawing-Story procedure allowed the establishment of three discussion axes: representations of baby, baby care and early separation process. This study concluded that the difficulties that permeate the context of caregivers' work are high turnover of institutionalized children, as well as employees, the difficulty of dealing with processes of bonding and breaking bonds and no recognition of the profession. We highlight that the place that these babies occupy in the imaginary of these caregivers influences the bond they establish with the children hence the care offered to the babies. It is also noteworthy that these caregivers exhibited anguish and suffering from the reasons they believed led the institutionalization.